Rancangan Aplikasi Sistem Reservasi Tamu Balai Besar Pelatihan Kesehatan Jakarta Kampus Hang Jebat Berbasis Web Dengan Metode Rapid Application Development (RAD) (Yayasan Kawanad, 2022)
The Jakarta Health Training Center, the Hang Jebat Campus, is a government agency that operates in the health training center to facilitate room reservations. So far, the Jakarta Health Training Center, the Hang Jebat campus, accepts reservations via telephone, fax, or consumers come directly to the Jakarta Health Training Center, Hang Jebat Campus. The purpose of this research is to build a web-based application program that is expected to have a very important impact in getting accurate and fast information and to design a web-based guest reservation application by making it easier for participants to make room reservations online and can control the number of training participants if it is limited to the maximum. So that the work becomes more effective in terms of time for reservations for both guests and receptionists. The system development method used is the Rapid Application Development (RAD) method. Based on the results of the study, to overcome the problems that exist in the Jakarta Health Training Center, Hang Jebat Campus, from the overall results of this study, it can be concluded that the Application Design of the Guest Reservation System for the Jakarta Health Training Center, Hang Jebat Campus, Guest reservation application at the Jakarta Health Training Center, Campus Hang Jebat is very interesting in terms of appearance because there are several features that are easy for guests and receptionists to understand.